188k views
3 votes
Hello, May I please get some assistance with this homework question? I posted an image below Q6

Hello, May I please get some assistance with this homework question? I posted an image-example-1

1 Answer

2 votes

Solution

Given the function 6x +3


\begin{gathered} \text{Let y = 6x + 3} \\ Replace\text{ x with y} \\ x\text{ =6y+3} \\ solve\text{ for y} \\ 6y\text{ =x-3} \\ \text{Divide both sides by 6} \\ y=\frac{x\text{ - 3}}{6} \\ \end{gathered}

Hence,


f^(-1)(x)\text{ =}(x-3)/(6)

User Robert Zahm
by
5.1k points